The Distribution of Income Shocks during Crises : An Application of Quantile Analysis to Mexico, 1992-95 - Maloney, William F.; Cunningham, Wendy V.; Bosch, Mariano (Washington, DC: World Bank, 2014)
Moving beyond the simple comparisons of averages typical of most analyses of household income shocks, this article employs quantile analysis to generate a complete distribution of such shocks by type of household during the 1995 crisis in Mexico. It compares the distributions across normal and crisis periods to see whether observed differences were due to the crisis or are intrinsic to the household types. Alternatively, it asks whether the distribution of shocks during normal periods was a reasonable predictor of vulnerability to income shocks during crises. It finds large differences in the distribution of shocks by household types both before and during the crisis but little change in their relative positions during the crisis. The impact appears to have been spread fairly evenly. Households headed by people with less education (poor), single mothers, or people working in the informal sector do not appear to experience disproportionate income drops either in normal times or during crises.